2013
DOI: 10.2489/jswc.68.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Paying for sediment: Field-scale conservation practice targeting, funding, and assessment using the Soil and Water Assessment Tool

Abstract: Watershed models have been widely used to estimate soil erosion and evaluate the effectiveness of conservation practices at different temporal and spatial scales; however, little progress has been made in applying these theoretical model results to the practical challenge of allocating conservation practice funding to meet specific soil loss objectives. Black Kettle Creek subwatershed (7,809 ha [19,295 ac]) of Little Arkansas River Watershed (360,000 ha [889,579 ac]) in south central Kansas was the focus of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…While SWAT is not often applied at the field scale, its base unit of calculation (the HRU) essentially provides fieldscale outputs, and previous studies have shown its usefulness at the field scale (Daggupati et al, 2011;Douglas-Mankin et al, 2013;Kalcic et al, 2015;Teshager et al 2016). HRUs are areas with the same soils, slope, and land use within a sub-basin and are lumped together for calculations.…”
Section: Extracting Swat Output At the Field Levelmentioning
confidence: 99%
See 3 more Smart Citations
“…While SWAT is not often applied at the field scale, its base unit of calculation (the HRU) essentially provides fieldscale outputs, and previous studies have shown its usefulness at the field scale (Daggupati et al, 2011;Douglas-Mankin et al, 2013;Kalcic et al, 2015;Teshager et al 2016). HRUs are areas with the same soils, slope, and land use within a sub-basin and are lumped together for calculations.…”
Section: Extracting Swat Output At the Field Levelmentioning
confidence: 99%
“…To our knowledge, this project is the first implementation of the Soil and Water Assessment Tool (SWAT) to assess agricultural conservation practice performance at the field scale for a P-based PFP program. While not specifically calling the program PFP, Douglas-Mankin et al (2013) described a program for "paying for sediment" reductions that was implemented in Black Kettle Creek watershed in Kansas, and it represents the most similar approach to our work with respect to modeling in a PFP system. Their work demonstrated the potential for PFP to achieve water quality improvements in a cost-effective and flexible manner.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Watershed models evaluate the hydrologic and water quality response to multiple BMPs at varying scopes and locations. Their application has also been expanded to the basin and regional scales [6]. For example, by incorporating Geographic Information System (GIS) techniques, cropland conversion to forest/grassland as an effective BMP can be easily evaluated by watershed models.…”
Section: Introductionmentioning
confidence: 99%